Comparison between Bi-2223 tape and RE-123 coated conductor from the view point of current transport properties influencing thermal stability. (December 2016) - Kiss, Takanobu; Inoue, Masayoshi; Higashikawa, Kohei; Suzuki, Takumi; Lyu, Lin; Takasaki, Ken; Imamura, Kazutaka; Onodera, Yuta; Uetsuhara, Dai; Ibi, Akira; Izumi, Teruo; Kitaguchi, Hitoshi
Highlights: Nonlinear flux flow dissipation in both Bi-2223 tape and RE-123 CC has been compared. Temperature rise and cooling power at over current condition have been analyzed. Spatial variation of local I c and its statistical distribution have been studied. Flux flow dissipation has been derived as a function of longitudinal coordinate. Abstract: We have investigated flux flow dissipation in typical two kinds of HTS tapes, i.e., a Bi-2223 multi-filamentary tape and a RE-123 coated conductor (CC) from the view point of heat load under over current conditions. Based on systematic measurements on current-voltage characteristics, the nonlinear flux flow dissipation has been described analytically by taking into account current sharing in metallic sheath or stabilization layer. Flux flow dissipation in the RE-123 CC shows much steeper temperature dependence than that of the Bi-2223 tape. As a result, attainable cooling power becomes smaller in the RE-123 CC in comparison with that of Bi-2223 tape even if the same cooling condition. In other word, acceptable temperature rise in the RE-123 CC is small at over current condition, whereas moderate temperature dependence in the Bi-2223 tape allows stable operation even if the bias current exceeds the critical current. Influence of spatial inhomogeneity in the both HTS tapes has also been investigated. Longitudinal variation of local critical current, I c, and its statistical behavior have been characterized by use of reel-to-reel scanning Hall probe microscopy. It has been found that the flux flow dissipation is possibly localized more than one order higher than that of the average value due to discrete local I c drops.